2020
DOI: 10.13189/app.2020.080302
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting Body of Pleurotus Ostreatus Reduces Serum Glucose and Modifies Oxidative Stress in Type 2 Diabetic: Drosophila Melanogaster (Fruit-Fly)

Abstract: Mushrooms, which possess medicinal properties, are also considered a good source of food and basic nutrients. Diabetic patients now use edible mushrooms as a source of low-calorie food. Mushrooms are used to treat and prevent diseases such as diabetes, obesity, heart disease, hyperacidity, cancer, hypertension and also act as immune modulators. In this study, the antidiabetic and antioxidant effects of the fruiting body of Pleurotus ostreatus (PO) in sucrose-induced type-2 diabetic Drosophila melanogaster was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Reactive Oxygen and Nitrogen Species (RONS) are highly reactive molecules generated within biological systems during normal cellular respiration or xenobiotic exposure [28,29]. Oxidative stress occurs when the generation of RONS molecules overwhelms the antioxidant mechanism of the body [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive Oxygen and Nitrogen Species (RONS) are highly reactive molecules generated within biological systems during normal cellular respiration or xenobiotic exposure [28,29]. Oxidative stress occurs when the generation of RONS molecules overwhelms the antioxidant mechanism of the body [30].…”
Section: Introductionmentioning
confidence: 99%
“…Research has proven that about 75% of the genes implicated in human diseases are well conserved in Drosophila melanogaster [32], making the model an excellent tool in toxicology and screening of nutraceuticals for medicinal activities [29]. Iojiim et al [33] recently reported that M. oleifera leaf supplementation significantly increased the survival rate and augmented in vivo functions of the antioxidant system in D. melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of Glutathione-S-transferase (GST; EC 2.5.1.18) was evaluated as described by Omale et al [21] utilizing 1-chloro-2, 4dinitrobenzene (CDNB) as substrate. The reaction mixture was made to 600 µL (solution A) by adding 20 µL of 0.25 M potassium phosphate buffer (pH 7.0 with 2.5 mM EDTA), 510 µL of 0.1 M GSH at 25°C, 60 µL of the dilute sample (distilled water to sample ratio 1:5), and 10µL of 25 mM CDNB.…”
Section: Glutathione-s-transferase (Gst) Activitymentioning
confidence: 99%
“…The body fights these free radicals through enzymatic (e.g., Superoxide dismutase, Catalase, Glutathione peroxidases) [19,20] or non-enzymatic antioxidants (e.g., Vitamins C & E, albumin, thiols) [20]. Thus, oxidative stress occurs when the rate of RONS production supersedes the natural antioxidant mechanisms of the body [21]. Oxidative stress is implicated in human diseases (e.g., Diabetes mellitus) [21] or xenobiotic exposures (e.g., highly active antiretroviral therapy (HAART) drugs) [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation